ON LACUNARY STATISTICAL BOUNDEDNESS OF ORDER ? OF GENERALIZED DIFFERENCE SEQUENCES - Temizsu, Fatih; Aydin, Abdullah; Mikail, Et; Inar, Muhammed (Univ Prishtines, 2024)
In this work, a new generalization of statistical boundedness is provided for difference sequences in regard to lacunary alpha-density and lacunary statistical sense. Apart from examining some inclusion theorems on related sequence spaces, we show that triangle(m)(theta)(S-b(alpha)) does not form a sequence algebra unlike S-theta(alpha)(b)
Keywords: Statistical boundedness; statistical convergence; p-Cesaro summabil- ity; difference sequences